The digital gaming handbook - Dillon, Roberto (Boca Raton : CRC Press, 2020)
The Digital Gaming Handbook covers the state-of-the-art in video and digital game research and development, from traditional to emerging elements of gaming across multiple disciplines. Chapters are presented with applicability across all gaming platforms over a broad range of topics, from game content creation through gameplay at a level accessible for the professional game developer while being deep enough to provide a valuable reference of the state-of-the-art research in this field. Key Features: International experts share their research and experience in game development and design Provides readers with inside perspectives on the cross-disciplinary aspects of the industry Includes retrospective and forward-looking examinations of gaming Editor: Dr. Roberto Dillon is a leading game studies educator with more than 15 years of experience in the field of game design and development.
Analyzing games with the AGE and 6-11 frameworks / Roberto Dillon -- Designing player interdependence to enhance players' social experience in multiplayer games / Katharina Emmerich -- Game accessibility : getting started / Thomas Westin, Ian Hamilton, Barrie Ellis -- Gamification for good : addressing dark patterns in gamified UX design / Ole Goethe -- The social media game : how gamification shapes our social media engagement / Dayana Hristova, Barbara Goebl, Suzana Jovicic, Thomas Slunecko -- Games for health / Andres Adolfo Navarro-Newball -- F2P mobile game design fundamentals / Simon Rozner -- Evergreen game design principles / Roberto Dillon -- Architectural spaces and level design in modern games / Christopher Totten -- Encouraging and rewarding repeat play of storygames / Alex Mitchell -- How we make mobile work : an indie perspective / James Barnard -- The development and UI design of an interactive game map / Tomasz Zawadzki, Slawomir Nikiel, Korneliusz Warszawski, Slawomir Krezel -- Challenges in designing and implementing a vector based 2D animation system / Jiang Jie, Seah Hock Soon, Liew Hong Ze, Chen Quan -- Best practices in pixel art / Cindy Lee -- Making sound decisions in game audio / Gwen Guo -- Making it real / Justing Ng, Andre' Pong -- Player locomotion in virtual reality games / Andrey Krekhov, Katharina Emmerich -- Working everywhere and nowhere : rules for a virtual office / Allan Simonsen -- A short summary of mobile games' history / Simon Rozner -- Retrogaming as a form of digital preservation : a cultural and technological approach / Marco Accordi Rickards, Micaela Romanini, Guglielmo De Gregori -- Diversity in games : how and why? / Alayna Cole.
OCLC-licensed vendor bibliographic record.
Keywords: Computer games; Computer games -- Design; Computer games -- Social aspects; Video games; Video games -- Design; Video games -- Social aspects; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design